Organizational and economic principles of creation and implementation of a circular business model of development - Dovgal, Olena (Вісник аграрної науки Причорномор'я, 2022)
The topicality of the topic is due to the problems of the essence and the basic principles of the formation and development of the circular economy. The well-known systems of circular economy principles 3R and 9R have been supplemented with new principles that more widely reveal the content and possibilities of transition to a closed-type economy. The purpose of the research is to determine improved organizational forms of closed-loop business models, developed on the basis of advanced principles of the circular economy, adapted to the realities of Ukraine. The research methodology consisted of a set of used methods, cognitive and systemic principles of research, a sequence of stages that included: the study of scientific literature, the analysis of the current state and international experience on issues of circular transformations, substantiation of one's own concept and organizational forms of a business model of a closed economy. The scientific work compares and summarizes the principles of circular economy development. Systematization of the classification features of types of circular business models proposed in modern practice has been carried out. On the basis of the conducted research, a scheme of the conceptual model of the R-economy is proposed. The main stages of implementing the circular business model in practical activities are proposed. The key advantages of the circular business model are defined as future long-term economic benefits that create additional potential for business competitiveness and contribute to solving public environmental problems. Based on the generalization, modern obstacles and socio-economic benefits from the transition to a circular model of development for business and society were identified. The modern practice of successful implementation of circular business models is analyzed. Proposals regarding the design of food production for the creation of a closed-type economic model are substantiated. Various archetypes of the organization of closed-type business models have been studied. The scheme of organizational forms of circular economy business models is presented, taking into account the specialty of the value chain, as one of its most effective mechanisms